10-Year Changes in Adiposity in Cameroon School-Age Children: Evidence for Increasing Central Adiposity and Higher Adiposity Levels in Tallest-for-Age Children. (15th October 2021) - Navti, Lifoter K.; Foudjo, Brice U. S.
Abstract : Objective . To examine changes in measures of adiposity and determine the prevalence of excess adiposity in relation to height in school children between 2010 and 2020. Methods . 5–12-year-old urban school-age children participated in two cross-sectional surveys in 2010 ( n = 1274) and 2020 ( n = 1550). Standard procedures were used for anthropometric measurements. Changes in BMI, waist circumference (WC), and waist-to-height ratio (WHtR) and the corresponding proportions of children with excess adiposity were analyzed and adjusted for design variables (class and school type) and age. Children were classified according to quartiles of height z-score and prevalence of excess adiposity estimated across each quartile. Results . There was a 2.4% and 3.3% increase in adjusted mean BMI and WC, respectively, between 2010 and 2020. The prevalence of central overweight/obesity (WC) and WHtR ≥ 0.5 increased by 7.3% ( X 2 = 27.151, p < 0.001 ) and 5.3% ( X 2 = 26.117, p < 0.001 ), respectively, between the two surveys except BMI overweight/obesity. The odds of excess adiposity significantly increased in 2020 for central overweight/obesity (WC) (OR 2.8, 95% CI 2.0–3.6) and WHtR ≥ 0.5 (OR 1.8, 95% CI 1.3–2.4) and not for BMI overweight/obesity (OR 1.3, 95% CI 0.8–1.7). The prevalence of BMI overweight/obesity significantly increased from 33% in 2010 to 51.5% in 2020 in the fourth quartile of height z-score ( X 2 = 19.198, p < 0.001 ). Similarly, the prevalence of central overweight/obesity (WC) significantly increased from 23.5% in 2010 to 42.4% in 2020 in the fourth quartile of height z-score ( X 2 = 18.733, p < 0.001 ). Conclusion . Central overweight/obesity has increased more than BMI overweight/obesity over the last decade. Children with a higher height-for-age tend to accumulate more adiposity. Objective monitoring of adiposity levels and height of children is needed in future to identify groups for targeted intervention and prevention of chronic diseases.